Trabalho e formação humana na ontologia do ser social de György Lukács - Daniel Handan Triginelli (2016)
From the immanent reading and analysis is intended to learn the work categories and Human Formation in the work to an ontology of social being of György Lukács. After grasp and understand these categories, it is intended to reproduce them accurately, showing, with strict fidelity, the genesis and the telos of lukacsiano thinking about these categories. As Lukacs, work at the same time based humans, ie allows to put in theworld becomes the center of the whole process of social development. From the ontological leap given in the work and various other complexes, as social in its essence (language, division of labor, etc.) appear in the material and historical process of human / social development. The being who sets to work achieves a superior condition compared to other species of nature, because, through the work, it can implement thetransformation of things in the natural state in a useful way the satisfaction of human needs. This is possible due to being objectified in things the optimal design that previously existed in his mind (the teleological capacity). In this movement the man promotes the transformation of nature and of himself. From the higher degree ofcomplexity that social life reaches, new needs arise, the division of labor is a real need for adequate social functioning, and since hunting is necessary that men perform teleological pores not designed for them (put teleological secondary). To work and transform the natural things and things with purpose to be social, we need to know the natural properties of such things to promote the best transformation, there has been the genesis of scientific development. The latter, in turn, helps the progress of the means of production. As the means of production are developed and enable increased production, it enables to exchange surplus, which results in conjunction with the division of labor,with the emergence of social classes, of class societies. At first slavery occurred as a social form of reproduction and domination, being superseded by feudal way the relationship was established between servants and masters, however, the highest degree of development occurred when the worker was separated from the means of productionand has become a commodity to be purchased in the market for the production in the capitalist system. But we must draw attention to the text studied composing the lukacsiano project to build a communist ethics that would help and demarcate certain needs of humanity incorporated outside the limits of capitalism. Similarly, the author seems to be interested in drafting such ethics in order to reform or transform and leadthe so-called Socialism Real to a new ethical aesthetics approaching more of what Lukacs seized as the authentic communism from, for he proposed, Marxism Renaissance.